Design of A Hvdc-Based Controller for Load Change Compensation and Stabilization of Inter-Area Oscillations - I. Ngamroo (Universitas Gadjah Mada, 2003)
As an interconnected power system via a High-Voltage Direct Current (HVDC) link is subjected to a rapid load change with the frequency of inter-area oscillation mode, system frequency and tie line power may be severely disturbed and oscillate. To compensate for the rapid load change and stabilize both frequency and tie line power oscillations due to the inter-area mode, the dynamic power flow control via a HVDC link can be exploited. To implement this concept, a new design method of HVDC-based controller is proposed. To grasp a physical characteristic of the inter-area oscillation frequency, the technique of overlapping decompositions is employed to achieve the subsystem embedded with the inter-area mode. Consequently, the second-order lead/lag controller of HVDC link can be designed in this subsystem. To acquire the desired overshoot of frequency oscillations, the parameters of the controller are automatically optimized by the Tabu Search (TS) algorithm. The effectiveness of the designed controller is investigated in a three-area longitudinal interconnected power system which represents the interconnection between the south of Thailand and Malaysia power systems.